The Performance of The Village Head in The Village Government Based on Law No. 6 of 2014 (Study on Mananggu Village, Boalemo Regency) - Lucyane Djaafar; Nopiana Mozin; Fauzia Rahma P. Amay (West Science Interdisciplinary Studies, 2023)
This study aims to determine the Performance of Village Heads in Village Development Based on Law No. 6 of 2014. The problem found is about how the village head performs in village development based on law no. 6 of 2014 and the factors that hinder the performance of village leaders in carrying out development in Mananggu Village, Mananggu District, Boalemo Regency. The method used in this study is qualitative research that uses descriptive descriptors, the subjects in the study are Village officials, and the community. With data collection techniques carried out by observation, interviews, and documentation. The results showed that the performance of the Mananggu village head still found several obstacles that hindered the development process of village government properly, these obstacles include: facilities and infrastructure are still lacking, lack of community participation, and inadequate human resources. Based on the results of the study, it can be concluded that the performance of the village head in village development is a serious problem that requires joint attention, which in its implementation requires cooperation between the village government and the community so that efforts and goals to advance the village can be carried out properly.